2020
DOI: 10.1007/978-3-030-37929-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Design Process

Abstract: the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Global Fashion Agenda (2017) projects that the consumption of apparel will increase by 63% by 2030, reaching 102 million tons. In the meantime, repurposing is a strategic way to extend product cycles by adding value in used garments (Eike et al, 2020). Presently, about one fifth of apparel goods are reused, recycled, or repurposed, with most apparel consumed ending in landfills (Kozlowski et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Global Fashion Agenda (2017) projects that the consumption of apparel will increase by 63% by 2030, reaching 102 million tons. In the meantime, repurposing is a strategic way to extend product cycles by adding value in used garments (Eike et al, 2020). Presently, about one fifth of apparel goods are reused, recycled, or repurposed, with most apparel consumed ending in landfills (Kozlowski et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some individuals choose to engage in consumer sustainable fashion practices, such as donating, swapping, mending, repurposing/redesigning, and others, that extend the life of their owned garments (Fletcher, 2016). The focus of this design and abstract aligns with repurposing, which is a process that utilizes discarded textiles to create new/renewed fashion products (Eike, et al, 2020), as it has been suggested as one solution to combat fashion overconsumption, and landfilled textile waste (Fletcher, 2008;Young et al, 2004). Additionally, size adjustable garments have been supported as a way to also reduce fashion waste (McKinney & Wei, 2020), particularly in childrenswear.…”
mentioning
confidence: 99%
“…Irick's (2013) dissertation outlined an initial process for repurposing that has since been expanded to include four levels of repurposing that build in complexity and skills needed to execute the intended design. These levels include: 1) re-style to repurpose, 2) subtractive repurposing 3) additive repurposing, and 4) intentional patternmaking to repurpose (Eike et al, 2020). For this experimental design, level four, was selected as the design method, where a discarded clothing item was deconstructed and new product patterns were purposefully designed and cut to maximize use of available fabric, working within existing shapes to produce a minimal or zero waste design.…”
mentioning
confidence: 99%